Phytochemistry and Uterine Contractile Effect of VLC Fractionated Bi-herbal Formulation “Makann” in Mice - Itemire, Anne Oghenekevwe; Idu, MacDonald; Enitome, Bafor Evi; Ofeimun, Josephine Omose; Gabriel, Benjamin Ogunma (Darul Yasin Al Sys, 2025)
This study evaluate the phytochemistry, uterine activity of a bi-herbal formulation of G. kola and C. papaya roots in rodents. Identification of phytochemical compounds in BH was done using high performance liquid chromatography (HPLC) and fractionated with vacuum liquid chromatography and thin layer chromatography. Ex-vivo BH elicited cumulative concentrations response on spontaneous contractions of oxytocin-induced contraction in the presence and absence of calcium and potassium induced contraction. The Phytochemicals showed alkaloids (Hordenine, Cytisine, Methyl Jasmonate, Galanthamine and an unidentified compound), flavonoids (benzoic acid, isoquercetin, rutin, chlorogenic acid and an unidentified compound), phenols (eugenol and ferulic acid) and cardiac glycosides (metildigoxin, cymarin and alpha-acetyldigoxin). The fractions were tested for spontaneous uterine contractions. Uterine contraction had an isncrease in amplitude spontaneous contractions with a steady decrease in frequency. In conclusion, the results obtained from this study adhere to the folklore report, validating its myometrial contractile response with the implicated phytoconstituents.